Ragna Crimson. 10 - Kobayashi, Daiki (Manga artist) (Square Enix Manga & Books, 2023)
"The final battle against the Blood of the Wing has begun! Ragna takes on Kamui, Golem teams up with Chimera to face down Borgius, and the Argentum Corps continues its desperate fight for survival versus Olto Zora. Meanwhile, having finally decided to play an active part in the conflict, Crimson confronts Ultimatia, setting the stage for a titanic clash between Winged Monarchs past and present!"--Back cover.